Estudo fitoquímico das raízes e do caule de Minasia alpestris (Asteraceae) e avaliação das atividades antimicrobianas de seus extratos frente a microrganismos da cavidade bucal - Keles, Larissa Costa (2008)
In this work is reported the phytochemical investigation of the crude dichloromethane extracts of the roots and stems of Minasia alpestris and the evaluation of their activities against oral pathogens using the broth microdilution method to determine the minimal inhibitory concentration (MIC). From the roots extract were identified 11 hydrocarbons (hexadecane, heptadecane, eicosane, tricosane, nonacosane, nonadecane, hentriancontane, tetratetracontane, 2-phenilundecane, 6 phenildodecane e 3-phenildodecane), 5 fatty acid esters (ethyl palmitate, ethyl esterate, ethyl nonadecanoate, ethyl oleate and ethyl linoleate), 5 triterpenes (α- amiryrin acetate, friedelin, lupeol acetate, pseudotaraxasterol acetate and lupenone) and piperonal by GC-MS. From the stems extract were identified by a fatty acid (palmitic acid), an homoterpene (6,10,14-trimethyl-pentadecan-2-one) and 5 triterpenes (β- amyrin, α amyrin, lupenone, lupeol and lupeol acetate). A sesquiterpene lactone (15 deoxygoyazensolide) was also isolated and its structure was elucidated using nuclear magnetic resonance techniques. Both of the extracts exhibited large values of MIC. Only the dichloromethane phase of the stems dichloromethane extract showed significative activity (MIC<100 µg/mL), however the compound isolated from it was not active (CIM>10µg/mL) against the microorganisms tested. Keywords: Minasia; 15-deoxygoyazensolide; antimicrobial activity.